Multiple linear regression and linear mixed models identify novel traits of salinity tolerance in Olea europaea L. (22nd November 2021) - Sodini, Mirko; Astolfi, Stefania; Francini, Alessandra; Sebastiani, Luca
Abstract: Olive can be considered as moderately tolerant to salinity, with marked differences among cultivars. In the present study, two olive cultivars with different salt tolerance, 'Leccino' (sensitive) and 'Frantoio' (tolerant), were treated with 120 mM of NaCl for 30 days. We measured the expression of genes involved in the management of sodium in the leaves, such as NHX, SOS1 and H + ATPase, and the concentration of Na +, K +, Mn 2+, Mg 2+ and Ca 2+ in the roots, bark, xylem and leaves of the olive plants. The results were analyzed with multiple linear models and mixed models. Furthermore, we utilized the analysis of covariance to find significant relationships in our data. Both cultivars significantly reduced net photosynthesis and increased water-use efficiency after 30 days of treatment. Sodium accumulated significantly in the roots of both cultivars, and 'Leccino' plants were also able to translocate it to the leaves and the bark. The NHX and vacuolar ATPase subunit E genes were significantly overexpressed in both the cultivars treated with NaCl. The SOS1, ATPase11 and ATPase8 genes were overexpressed in 'Frantoio'. The covariance between gene expression and element concentrations data was analyzed to identify significant interactions between cultivars and treatments. Na + accumulation in the roots of 'Frantoio' was positively related to the accumulation of K +, Mn 2+, Mg 2+ and Ca 2+ in the xylem, bark and leaves. 'Frantoio' capability to mobilize elements, especially Ca 2+, together with the overexpression of key genes for sodium management, could be crucial for salt tolerance.